PENCEGAHAN STUNTING MELALUI EDUKASI NUTRISI DAN POLA MAKAN SEHAT IBU HAMIL - Cindy Aulia Rachelli; Sumarti Endah Purnamaningsih Maria Margaretha; Siti Maryati; Budi Punjastuti; Amri Wulandari (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Stunting remains a significant public health issue in Indonesia, primarily caused by inadequate maternal nutrition during pregnancy. Nutritional education for pregnant women is a critical strategy to prevent stunting in infants. This community service activity was conducted in Desa Manukan, Sendangsari, Pajangan, Kabupaten Bantul, targeting 40 pregnant women. Methods included educational lectures, interactive discussions, and healthy menu simulations to enhance participants’ knowledge and skills in applying balanced dietary practices. Evaluation was conducted through question-and-answer sessions and observation of participant engagement. Results indicated significant improvements in understanding maternal nutritional needs, recognition of nutritious foods, planning healthy daily menus, and knowledge of stunting prevention. Observational data showed that most participants actively engaged in discussions and were capable of preparing healthy menus following balanced nutrition principles. Practical, simulation-based education proved effective in strengthening participants’ preparedness to maintain maternal and infant health. This activity underscores the importance of community-based nutritional interventions during pregnancy to reduce the risk of stunting.